Terapi Non Farmakologi Berbasis Sumber Hewani Lebih Efektif untuk Mengatasi Anemia pada Remaja Putri - Didhing Supariti; Siti Aisah; Satriya Pranata (FORIKES, 2024)
Anemia is one of the health problems that are often found in adolescents. This can be influenced by several factors such as nutritional deficiencies to bleeding due to menstruation. Currently, non-pharmacological actions have been developed to overcome anemia in adolescent girls by using foods from plant and animal sources. This study aimed to compare non-pharmacological therapies from plant and animal sources in overcoming anemia in adolescent girls. The method used in this study was a systematic review. The literature came from Dimensions AI. The search was carried out with the keywords: (Complementary therapy AND hemoglobin AND anemia AND adolescent girls, Complementary therapy AND hemoglobin AND anemia AND adolescent girls, Non pharmacology AND hemoglobin AND anemia AND adolescent girls). The article selection process is based on the PRISMA flow diagram. Based on the results of the selection and evaluation, 12 eligible articles were obtained. The review results showed significant non-pharmacological therapy to overcome anemia in adolescent girls, with p values respectively: 1) plant sources: dates = 0.000, red guava 0.001, moringa leaves = 0.001, green beans = 0.000, dragon fruit = 0.000, beetroot = 0.000, avocado = 0.000 and soybeans = 0.000; 2) animal sources: chicken liver = 0.000, chicken eggs = 0.000, quail eggs = 0.000 and honey = 0.000. It was concluded that animal sources are more effective in overcoming anemia in adolescent girls.Keywords: non-pharmacological intervention, hemoglobin, adolescent girls ABSTRAK Anemia merupakan salah satu masalah kesehatan yang banyak ditemukan pada golongan remaja. Hal ini dapat dipengaruhi oleh beberapa faktor seperti kekurangan nutrisi hingga pendarahan akibat menstruasi. Saat ini telah berkembang tindakan non farmakologis untuk mengatasi anemia pada remaja putri dengan menggunakan makanan dari sumber dari nabati dan hewani. Studi ini bertujuan untuk membandingkan terapi non farmakologi dari sumber nabati dan hewani dalam mengatasi anemia pada remaja putri. Metode yang digunakan dalam studi ini adalah systematic review. Literatur berasal dari Dimensions AI. Pencarian dilakukan dengan kata kunci: (Terapi komplementer AND hemoglobin AND anemia AND remaja putri, Complementary therapy AND hemoglobin AND anemia AND adolescent girls, Non farmakologi AND hemoglobinAND anemia AND remaja putri, Non pharmacology AND hemoglobin AND anemia AND adolescent girls). Proses pemilihan artikel didasarkan pada diagram alir PRISMA. Berdasarkan hasil seleksi dan evaluasi didapatkan 12 artikel yang layak. Hasil review menunjukkan terapi non farmakologi yang signifikan untuk mengatasi anemia pada remaja putri, dengan nilai p masing-masing adalah: 1) sumber nabati: kurma = 0,000, jambu biji merah 0,001, daun kelor = 0,001, kacang hijau = 0,000, buah naga = 0,000, bit = 0,000, alpukat = 0,000 dan kedelai = 0,000; 2) sumber hewani: hati ayam = 0,000, telur ayam = 0,000, telur puyuh = 0,000 dan madu = 0,000. Disimpulkan bahwa sumber hewani lebih efektif untuk mengatasi anemia pada remaja putri.Kata kunci: intervensi non farmakolgi, hemoglobin, remaja putri